1999
DOI: 10.1021/la981769g
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Ionic and Nonionic Surfactants in the Adsorbed Film and Micelle:  Hydrochloric Acid, Sodium Chloride, and Tetraethylene Glycol Monooctyl Ether

Abstract: The aqueous solutions of hydrochloric acid−tetraethylene glycol monooctyl ether (C8E4) and sodium chloride−C8E4 mixtures were investigated to examine the interaction between inorganic ions and nonionic surfactants both in the adsorbed film and micelle. Their surface tension was measured as a function of the total molality of the inorganic electrolyte and C8E4 mixture and the composition of C8E4. The results of surface tension measurement were analyzed by our thermodynamic procedure, and the phase diagrams of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…4 into Eqs. [6] and [8] and are shown as a function ofX 2 at constant γ together with theˆ H . Furthermore, taking into acccount the dependence ofX H 2 on γ in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 into Eqs. [6] and [8] and are shown as a function ofX 2 at constant γ together with theˆ H . Furthermore, taking into acccount the dependence ofX H 2 on γ in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to this idea, however, we have applied the thermodynamic treatment of surfactant mixtures to the sodium chloride, NaCl, and dodecylammonium chloride (DAC) mixture and clarified the miscibility of NaCl and DAC in the adsorbed film and micelle (5). Furthermore, the treatment has been applied to the NaCl and tetraethylene glycol monooctyl ether (C 8 E 4 ) mixture to elucidate an origin of the strong nonideal interaction between ionic and nonionic surfactants in the adsorbed film and micelle (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the measured values for a sample solution scatter in disorder or not, depends in most cases on the chemical species (especially on the structure) or its concentration. Aratono and his coworkers who have developed the drop volume method in collaboration with Yamashita Giken have reported that the accuracy of this drop volume method has been confirmed to be sufficiently high from comparison with the results determined by the most reliable method of image analysis of pendant drop 41) .…”
Section: Methodsmentioning
confidence: 95%
“…The fundamental question is how one can increase the metal ion density to 6-7 metal ion/C n EO m mole ratios without disturbing the LC phase. It is known that charge surfactants, such as CTAB and SDS can be used together with the non-ionic surfactants or Pluronics in the LLC mesophases and micelle phases [19][20][21][22][23][24][25]. The hydrophobic interactions (among alkyl chains of both charged and non-ionic surfactants) and the hydration of the alky tail-ethylene oxide interface with the help of a charged head group enable the assembly of two or three surfactants into a single mesophase.…”
Section: Introductionmentioning
confidence: 99%